Auditoria de inventarios en la lubricadora “Lubricomercio Luna” en el periodo 2023-2024. - Cherrez Salas, Lourdes Gabriela (Machala : Universidad Técnica de Machala, 2025)
The purpose of this study is to analyze the relationship between inventory control and the reliability of accounting records at the company Lubricomercio Luna during the 2023 and 2024 fiscal periods. The research is conducted under a mixed-methods approach, using quantitative techniques through a structured observation guide and qualitative techniques through a semi-structured interview with the accounting department. The objective was to assess compliance with documentary, operational, and regulatory procedures, as well as to identify deficiencies affecting the accuracy of financial information. The results show a partial improvement in inventory management, with compliance increasing from 36.36% in 2023 to 54.55% in 2024, highlighting progress in document control. However, significant weaknesses remain in operational procedures and regulatory compliance. The company does not apply formal valuation methods nor performs regular reconciliations between physical and accounting records, which impacts the transparency and reliability of its data. From a theoretical standpoint, the study is based on IAS 2, International Standards on Auditing, and the COSO model, which support the importance of implementing structured internal controls and periodic audits to optimize inventory management. The conclusions suggest the need to implement procedure manuals, digitize records, and train personnel to strengthen traceability and decision-making. This study offers a technical proposal that can be replicated in other microenterprises facing similar challenges.
El presente estudio tiene como finalidad analizar la relación entre el control de inventarios y la confiabilidad de los registros contables en la empresa Lubricomercio Luna, durante los periodos fiscales 2023 y 2024. La investigación se desarrolla bajo un enfoque mixto, utilizando técnicas cuantitativas mediante una guía de observación estructurada y técnicas cualitativas a través de una entrevista semiestructurada al área contable, el objetivo fue evaluar el cumplimiento de los procedimientos documentales, operativos y normativos, así como identificar deficiencias que inciden en la exactitud de la información financiera. Los resultados evidencian una mejora parcial en la gestión de inventarios, al pasar de un 36,36 % de cumplimiento en 2023 a un 54,55 % en 2024, destacando avances en el control documental, aunque persisten debilidades significativas en los procedimientos operativos y en el cumplimiento normativo. La empresa no aplica métodos formales de valuación ni realiza conciliaciones periódicas entre lo físico y lo contable, lo que afecta la transparencia y confiabilidad de sus registros. Desde la fundamentación teórica, se recurre a la NIC 2, las Normas Internacionales de Auditoría y el modelo COSO, los cuales respaldan la importancia de establecer controles internos estructurados y auditorías periódicas para optimizar la gestión de inventarios, las conclusiones sugieren la necesidad de implementar manuales de procedimientos, digitalizar los registros y capacitar al personal para fortalecer la trazabilidad y la toma de decisiones. Este estudio ofrece una propuesta técnica replicable en otras microempresas con problemas similares.
Keywords: AUDITORIA DE INVENTARIOS; CONTROL INTERNO; REGISTROS CONTABLES